719 The Effect of a Fish-Oil-Based Lipid Emulsion on the Parenteral Nutrition-Associated Liver Disease in Very Low Birth Weight Infants. (October 2012) - Chang, M; Kang, H
Abstract : Background and Aims: Prolonged parenteral nutrition (PN) can cause parenteral nutrition-associated liver disease (PNALD) in very low birth weight infants (VLBWIs). Evidence has suggested soybean-oil-based lipid emulsion (SOLE) is a contributing factor to the development of PNALD. In this study, we investigated the effect of fish-oil-based lipid emulsion (FOLE) on incidence and severity of PNALD in VLBWIs compared with SOLE. Methods: Retrospective review of 66 VLBWIs who received PN for more than 14 days in our NICU from January 2007 to December 2010 was performed. Patients were divided into two groups: SOLE Group (n=30, January 2007–March 2009), received Intralipid® (Choongwae Pharma Corporation, Seoul, Korea) and FOLE group (n=36, June 2009–December 2010), received SMOFlipid® (Fresenius Kabi AG, Bad Homburg, Germany). The Clinical and laboratory findings were evaluated. Results: There were no significant differences in the demographic features and major morbidities between two groups. The peak level of serum direct bilirubin were markedly lower in the FOLE group compared with the SOLE group (2.21±2.16 vs. 3.16±2.20 mg/dL, p =0.011). And the peak level of AST (68.72±68.00 vs. 106.67±79.09 IU/L, p =0.008) and ALT (30.92±29.72 vs. 53.70±40.86 IU/L, p =0.002) were significant lower in the FOLE group compared with the FOLE group. However, the peak levels of serum triglyceride were similar. (245.22±128.47 vs. 226.97±99.49 mg/dL, p =0.747). Conclusions: The use of FOLE in VLBW infants may reduce the risk of PNALD.